Penerapan Budaya Hidup Sehat Untuk Peningkatan Kualitas Kesehatan Anak Sekolah Dasar Dalam Mengembangkan Kebiasaan Makan Sehat Budaya Lokal Dan Praktik Kebersihan Diri - Nadila Siswanti; Nelli Amanda Sari; Dhea Syakira; Padilah Hoiriah; Suyono Suyono (Mathematics Education Study Program, 2025)
This study aims to develop a local culture-based healthy living model to increase the awareness of SDN 06093 students about healthy eating habits and personal hygiene. The method used was a simple intervention based on local culture, which involved the introduction of healthy traditional foods and personal hygiene practices in full-day activities. The results showed that this approach was effective in improving students' understanding of the importance of healthy eating habits and hand washing. This model makes an important contribution to the development of practical culture-based health education strategies, especially in resource-limited settings.